The Anxiety of Pregnant Women in Post Abortion by Reading Ayatus Syifa and Lavender Aromatherapy - Inna Sholicha Fitriani; Nurhidayati Nurhidayati (STIKes Patria Husada Blitar, 2020)
Pregnancy and abortion can be a stressor that can increase anxiety. The Qur'an is just as a doubt antidote and diseases that are in the chest and it is commonly known as the heart. The Lavender one of essential oil which popular and it is widely used in the field of clinical health which especially addressing psychosomatic in gynecology. The purpose of this research was to determine the potential decrease of anxiety on pregnant women in post-abortion by reading verses syifa and lavender aromatherapy. The research used experimental design of Pre and Post Test-Group with a sample of all pregnant women who had abortion. The total sample was 24 people. The research was conducted in Aisyiyah Hospital and Muhammadiyah Hospital of Ponorogo in Juny - August 2018. The data analysis used T and Wilcoxon test. The result of data analysis were 0,003 <0,05 and there was comparison between potential decrease of anxiety in pregnant women post abortion by reading verses syifa and giving aromatherapyÂ of lavender. Â The comparison showed that the potency of decreasing of anxiety in pregnant woman post abortion by reading ayatus syifa and giving aromatherapy of lavender, 38% decreased anxiety level in pregnant woman post abortion because of lavender therapy and 62% was due to other factor. Then 89%decreased in anxiety level in pregnant woman post abortion because of reading ayatus syifa and 11% due to other factor. Research products can be used as media in the treatment of non pharmacological psikomatic in order to support quality of public health.